A novel protein tyrosine phosphatase like phytase from Lactobacillus fermentum NKN51: Cloning, characterization and application in mineral release for food technology applications. (February 2018) - Sharma, Rekha; Kumar, Piyush; Kaushal, Vandana; Das, Rahul; Kumar Navani, Naveen
Graphical abstract: Highlights: Study reports first molecular evidence of phytase enzyme from genus Lactobacillus . Novel PTP like phytase ( phyLf ) was cloned and expressed from L. fermentum NKN51. PhyLf exhibited high substrate specificity and resistance against oxidation by ROS. Phylf retains efficient dephytinization ability under gastric conditions. PhyLf from GRAS organism offers potential applications in food industries. Abstract: A novel protein tyrosine phosphatase like phytase (PTPLP), designated as PhyLf from probiotic bacterium Lactobacillus fermentum NKN51 was identified, cloned, expressed and characterized. The recombinant PhyLf showed specific activity of 174.5 U/mg. PhyLf exhibited strict specificity towards phytate and optimum temperature at 60 °C, pH 5.0 and ionic strength of 100 mM. Km and Kcat of PhyLf for phytate were 0.773 mM and 84.31 s −1, respectively. PhyLf exhibited high resistance against oxidative inactivation. PhyLf shares no homology, sans the active site with reported PTLPs, warranting classification as a new subclass. Dephytinization of durum wheat and finger millet under in vitro gastrointestinal conditions using PhyLf enhanced the bioaccessibility of mineral ions. Probiotic origin, phytate specificity, resistance to oxidative environment and gastric milieu coupled with ability to release micronutrients are unique properties of PhyLf which present a strong case for its use in ameliorating nutritional value of cereals and animal feed.